HIV and Addiction Services for People Who Inject Drugs: Healthcare Provider Perceptions on Integrated Care in the U.S. South - Davis Bradford; Mariel Parman; Sera Levy; Wesli H. Turner; Li Li; Leah Leisch; Ellen Eaton; Kaylee B. Crockett (SAGE Publishing, 2023)
This qualitative study evaluates physician training and experience with treatment and prevention services for people who inject drugs (PWID) including medications for opioid use disorder (MOUD) and HIV pre-exposure prophylaxis (PrEP). The Behavioral Model of Healthcare Utilization for Vulnerable Populations was applied as a framework for data analysis and interpretation. Two focus groups were conducted, one with early career physicians (n = 6) and one with mid- to late career physicians (n = 3). Focus group transcripts were coded and analyzed using thematic analysis to identify factors affecting implementation of treatment and prevention services for PWID. Respondents identified that increasing the availability of providers prescribing MOUD was a critical enabling factor for PWID seeking and receiving care. Integrated, interdisciplinary services were identified as an additional resource although these remain fragmented in the current healthcare system. Barriers to care included provider awareness, stigma associated with substance use, and access limitations. Providers identified the interwoven risk factors associated with injection drug use that must be addressed, including the risk of HIV acquisition, notably more at the forefront in the minds of early career physicians. Additional research is needed addressing the medical education curriculum, health system, and healthcare policy to address the addiction and HIV crises in the U.S. South.